2012
DOI: 10.1007/s10741-012-9305-3
|View full text |Cite
|
Sign up to set email alerts
|

Rodent models of heart failure: an updated review

Abstract: Heart failure (HF) is one of the major health and economic burdens worldwide, and its prevalence is continuously increasing. The study of HF requires reliable animal models to study the chronic changes and pharmacologic interventions in myocardial structure and function and to follow its progression toward HF. Indeed, during the past 40 years, basic and translational scientists have used small animal models to understand the pathophysiology of HF and find more efficient ways of preventing and managing patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 310 publications
(185 reference statements)
2
64
0
2
Order By: Relevance
“…Abdominal aortic constriction (banding) surgeries were performed on 4-week-old male Wistar rats weighing 120~150 g. This is a well-established surgical technique for induction of LV chronic pressure overload, hypertrophy, and HF in rodents [10]. The banding initially imposes little or no restriction to aortic flow, but gradually, as the animal grows, the relative severity of the constriction increases, resulting in cardiac hypertrophy.…”
Section: Pressure-overload-induced Hf Modelmentioning
confidence: 99%
“…Abdominal aortic constriction (banding) surgeries were performed on 4-week-old male Wistar rats weighing 120~150 g. This is a well-established surgical technique for induction of LV chronic pressure overload, hypertrophy, and HF in rodents [10]. The banding initially imposes little or no restriction to aortic flow, but gradually, as the animal grows, the relative severity of the constriction increases, resulting in cardiac hypertrophy.…”
Section: Pressure-overload-induced Hf Modelmentioning
confidence: 99%
“…Studies have shown that the mean arterial blood pressure is significantly decreased immediately after the construction of an AVF [3, 9, 28, 29], and after 4 weeks, significant cardiac hypertrophy develops, with near-normal function at 4 weeks [9, 29]. In the current study, only SBP was measured at baseline and at the 1-week follow-up, because noninvasive pressure measurement systems are more sensitive when measuring SBP.…”
Section: Discussionmentioning
confidence: 96%
“…Rodent models are appropriate fistula models, because of the demanding technical and financial requirements for using large animals as well as due to the difficulty of establishing mixed-disease models in these animals [5, 9, 10]. Many models were described in rats, such as the aortocaval model, the tail model, and the femoral model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations with human cardiac tissue are overcome, with varying degrees of success, by the use of patient-mimicking animal models [8,9] in which HFpEF is developed as a consequence of spontaneous and experimentally induced hypertension or metabolic syndromes (obesity and diabetes). The results of these and other cross-sectional studies showed that LV diastolic dysfunction conditions can be associated with: (1) fluctuation in cardiac calcium-handling protein levels [10], (2) alterations in proteins, which play an important role in maintaining the sarcomeric structure and functionality [11][12][13], and (3) aberrant extracellular matrix protein turnover [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%